Assessment of the effect of urethral plate width on outcome of hypospadias repair. Issue 6 (December 2019) - Chukwubuike, K.E.; Obianyo, N.E.N.; Ekenze, S.O.; Ezomike, U.O.
Summary: Background: The paradigm for hypospadias repair is a straight penis with a vertical meatus at the tip of the glans that provides satisfactory urination and is cosmetically acceptable to the parents of the patient. Objective: To determine the cosmetic and functional outcomes of hypospadias repair in relation to the width of the urethral plate. Patients and methods: This study was a prospective evaluation of patients operated for hypospadias. The urethral plate width (UPW) of the patients were measured preoperatively using vernier calipers. The patients were categorized into groups A and B. Group A patients have a UPW <8 mm, whereas group B patients have a UPW ≥8 mm. The width of the urethral plate was correlated to the cosmetic outcome (using hypospadias objective penile evaluation [HOPE]) and functional outcome (using the urinary stream) of hypospadias repair. Results: Overall, 47 patients had their hypospadias repaired during the study period. But, only 42 patients who had their distal hypospadias repaired using tubularized incised plate urethroplasty were evaluated. There were 20 patients (47.6%) in group A and 22 patients (52.4%) in group B, with a mean urethral plate of 7.3 mm ± 0.50 SD. The mean UPW in group A was 5.6 mm ± 1.22 SD and the mean UPW in group B was 8.8 mm ± 0.88 SD. Overall, mean HOPE score was 40.0 ± 6.83 SD. Group A patients had a mean HOPE score of 38.7 ± 7.49 SD, whereas Group B patients had a mean HOPE score of 41.2 ± 6.08 SD. P -value was 0.725, which is not statistically significant. Relating good urinary stream (15 in group A and 20 in group B) with the width of the urethral plate statistically (using Spearman correlation technique) gave a P -value of 0.03 ( P  < 0.05), which is statistically significant. Conclusion: Our findings indicate that the cosmetic outcome of hypospadias repair may not be determined by UPW, but the functional outcome may be predicted by the width of the urethral plate. Table HOPE and UP width of the two groups (their means and SDs). Table   Group A Group B Mean SD Mean SD HOPE 38.7 7.49 41.2 6.08 UP width 5.6 1.22 8.8 0.88 HOPE, hypospadias objective penile evaluation; SD, standard deviation; UP, urethral plate.